Interobserver variability in target definition for stereotactic arrhythmia radioablation - van der Ree, Martijn H.; Cuculich, Phillip S.; van Herk, Marcel; Hugo, Geoffrey D.; Balt, Jippe C.; Bates, Matthew; Ho, Gordon; Pruvot, Etienne; Herrera-Siklody, Claudia; Hoeksema, Wiert F.; Lee, Justin; Lloyd, Michael S.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Stereotactic arrhythmia radioablation (STAR) is a potential new therapy for patients with refractory ventricular tachycardia (VT). The arrhythmogenic substrate (target) is synthesized from clinical and electro-anatomical information. This study was designed to evaluate the baseline interobserver variability in target delineation for STAR. Methods: Delineation software designed for research purposes was used. The study was split into three phases. Firstly, electrophysiologists delineated a well-defined structure in three patients (spinal canal). Secondly, observers delineated the VT-target in three patients based on case descriptions. To evaluate baseline performance, a basic workflow approach was used, no advanced techniques were allowed. Thirdly, observers delineated three predefined segments from the 17-segment model. Interobserver variability was evaluated by assessing volumes, variation in distance to the median volume expressed by the root-mean-square of the standard deviation (RMS-SD) over the target volume, and the Dice-coefficient. Results: Ten electrophysiologists completed the study. For the first phase interobserver variability was low as indicated by low variation in distance to the median volume (RMS-SD range: 0.02-0.02cm) and high Dice-coefficients (mean: 0.97±0.01). In the second phase distance to the median volume was large (RMS-SD range: 0.52-1.02cm) and the Dice-coefficients low (mean: 0.40±0.15). In the third phase, similar results were observed (RMS-SD range: 0.51-1.55cm, Dice-coefficient mean: 0.31±0.21). Conclusions: Interobserver variability is high for manual delineation of the VT-target and ventricular segments. This evaluation of the baseline observer variation shows that there is a need for methods and tools to improve variability and allows for future comparison of interventions aiming to reduce observer variation, for STAR but possibly also for catheter ablation.